2006
DOI: 10.1074/jbc.m607114200
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Prokaryotic Type I GTP Cyclohydrolase Family

Abstract: GTP cyclohydrolase I (GCYH-I) is the first enzyme of the de novo tetrahydrofolate biosynthetic pathway present in bacteria, fungi, and plants, and encoded in Escherichia coli by the folE gene. It is also the first enzyme of the biopterin (BH4) pathway in Homo sapiens, where it is encoded by a homologous folE gene. A homology-based search of GCYH-I orthologs in all sequenced bacteria revealed a group of microbes, including several clinically important pathogens, that encoded all of the enzymes of the tetrahydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 50 publications
2
69
0
Order By: Relevance
“…IVIAT also indentified enzymes involved in the synthesis of cell molecules, including amino acids, pyrimidine, and alginate. These results are consistent with those discovered using IVIAT with other organisms (12,(17)(18)(19)(20)(21), including identical proteins and proteins with a similar function, such as folE, which is a GTP cyclohydrolase I essential for folate synthesis (35), and narV, narY, and narW, which are located in the narZYWV locus encoding nitrate reductase 2 and are involved in the biochemical reaction of reducing nitrate (36).…”
Section: Fig 1 In Vivo Gene Expression At 24 H and 48 H Relative To Tsupporting
confidence: 90%
“…IVIAT also indentified enzymes involved in the synthesis of cell molecules, including amino acids, pyrimidine, and alginate. These results are consistent with those discovered using IVIAT with other organisms (12,(17)(18)(19)(20)(21), including identical proteins and proteins with a similar function, such as folE, which is a GTP cyclohydrolase I essential for folate synthesis (35), and narV, narY, and narW, which are located in the narZYWV locus encoding nitrate reductase 2 and are involved in the biochemical reaction of reducing nitrate (36).…”
Section: Fig 1 In Vivo Gene Expression At 24 H and 48 H Relative To Tsupporting
confidence: 90%
“…Thus, the derepression of all4725 under zinc limitation would probably lead to the replacement of a zinc-dependent porphobilinogen synthase (All4380) by a zinc-independent one (All4725), under conditions in which the former is most probably inactive. Replacement of zinc-dependent proteins by zinc-independent isoforms seems to be a common strategy in a variety of prokaryotes (5,16,21,31,50).…”
Section: Discussionmentioning
confidence: 99%
“…Haloferax volcanii is one of the rare archaea with both active folate and G + pathways (Gupta 1984, Gupta 1986, Ortenberg et al 2000; however, no folE gene has been identified in its genome. Instead, H. volcanii possesses a folE2 gene (HVO_2348) encoding a newly discovered GTP cyclohydrolase enzyme IB that is involved in archaeosine biosynthesis (El Yacoubi et al 2006, Phillips et al 2008. A role in folate biosynthesis has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%